2012
DOI: 10.3390/md10091977
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-Inflammatory Activities of Crude Methanolic Extract of Red Alga Bryothamnion triquetrum

Abstract: The marine environment is an extraordinary reservoir of bioactive natural products, many of which exhibit chemical and structural features not found in terrestrial natural products. In this regard, the aim of this study was to investigate the possible antinociceptive and anti-inflammatory activities of a crude methanolic extract of the red alga Bryothamnion triquetrum (BT-MeOH) in murine models. Groups of Swiss mice of both sexes (25–30 g) were used throughout the experiments. The potential antinociceptive of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 77 publications
(82 reference statements)
0
14
0
Order By: Relevance
“…For example, a methanol extract of Bryothamnion triquetrum [62] had both antinociceptive and anti-inflammatory properties in experiments that used Swiss mice. Antinociceptive activity was examined using an acetic acid-induced writhing test, a hot-plate test, and glutamate-/formalin-induced nociception.…”
Section: Anti-inflammatory and Antinociceptive Properties Of Marine Amentioning
confidence: 99%
“…For example, a methanol extract of Bryothamnion triquetrum [62] had both antinociceptive and anti-inflammatory properties in experiments that used Swiss mice. Antinociceptive activity was examined using an acetic acid-induced writhing test, a hot-plate test, and glutamate-/formalin-induced nociception.…”
Section: Anti-inflammatory and Antinociceptive Properties Of Marine Amentioning
confidence: 99%
“…A number of publications during 2012–2013 reported extracts or structurally uncharacterized marine compounds, with novel and interesting preclinical and/or clinical pharmacology: in vitro antimalarial activity in crude extracts from Fiji marine organisms using a semi-automated RNA fluorescence-based high-content live cell-imaging assay [10]; the first report of in vitro liver stage antiplasmodial activity and dual stage inhibitory potential of British seaweeds [11]; anti-hepatitis C virus activity affecting the viral helicase NS3 and replication, in crude extracts from the marine feather star Alloeocomatella polycladia [12]; anti-herpes simplex virus HSV-1 and HSV-2 activity in a purified sulfoglycolipid fraction from the Brazilian marine alga Osmundaria obtusiloba [13]; in vivo anti-inflammatory activity of a heterofucan from the Brazilian seaweed Dictyota menstrualis that inhibited leukocyte migration to sites of tissue injury by binding to the cell membrane [14]; in vivo antinociceptive and anti-inflammatory activity in a crude methanolic extract of the red alga Bryothamnion triquetrum [15]; in vivo anti-inflammatory activity in a sulfate polysaccharide fraction from the red alga Gracilaria caudata resulting in significant inhibition of neutrophil migration and cytokine release [16]; in vitro anti-inflammatory effect of a hexane-soluble fraction of the brown alga Laminaria japonica that inhibited nitric oxide, prostaglandin E 2 , interleukin (IL)-1β and IL-6 release from lipopolysaccharide-stimulated macrophages via inactivation of nuclear factor-κB transcription factor [17]; in vivo anti-inflammatory of a polysaccharide-rich fraction from the marine red alga Lithothamnion muelleri that reduced organ injury and lethality, as well as pro-inflammatory cytokines and chemokines, associated with graft-versus-host disease in mice [18]; in vivo clinical effectiveness in an osteoarthritis trial by PCSO-524 TM , a nonpolar lipid extract from the New Zealand marine green lipped mussel Perna canaliculus , which may offer “potential alternative complementary therapy with no side effects for osteoarthritis patients” [19]; enhanced antioxidant activity of chitosan nanoparticles as compared to chitosan on hydrogen peroxide-induced stress injury in mouse macrophages in vitro [20]; induction of concentration-dependent vasoconstrictive activity on isolated rat aorta by a tentacle extract from the jellyfish Cyanea capillata [21]; significant antioxidant effect of a sulfated-polysaccharide fraction of the marine red alga Gracilaria birdiae which prevented naproxen-induced gastrointestinal damage in rats by reversing glutathione depletion [22]; in vitro antioxidant properties of a polysaccharide from the brown seaweed Sargassum graminifolium (Turn.) that was also observed to inhibit calcium oxalate crystallization, a constituent of urinary kidney stones [23]; antioxidant activity in organic extracts from 30 species of Hawaiian marine algae, with the carotenoid fucoxanthin identified as the major bioactive antioxidant compound in the brown alga T. ornata [24]; screening of antioxidant activity in 18 cyanobacteria and 23 microalgae cell extracts identified Scenedesmus obliquus strai...…”
Section: Introductionmentioning
confidence: 99%
“…Our research group reported some pharmacological activities of marine algae and their secondary metabolites [16,30,31,32]. Recently, we described the antinociceptive activity of caulerpine [16].…”
Section: Introductionmentioning
confidence: 99%